2022
DOI: 10.1101/2022.01.06.475270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional oscillation of a multienzyme glucosome assembly during cell cycle progression

Abstract: Glucose metabolism has been studied extensively to understand functional interplays between metabolism and a cell cycle. However, our understanding of cell cycle-dependent metabolic adaptation particularly in human cells remains largely elusive. Meanwhile, human enzymes in glucose metabolism are shown to functionally organize into three different sizes of a multienzyme metabolic assembly, the glucosome, to regulate glucose flux in a size-dependent manner. Here, using fluorescence single-cell imaging techniques… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Collectively, we demonstrate that the biological properties of PFKL which would be intrinsically under controls by various cellular processes, including but not limited to signaling pathways (Jeon et al, 2022a) and a cell cycle (Jeon et al, 2022b), are critical determinants at the initiation step for glucosome formation in human cells.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Collectively, we demonstrate that the biological properties of PFKL which would be intrinsically under controls by various cellular processes, including but not limited to signaling pathways (Jeon et al, 2022a) and a cell cycle (Jeon et al, 2022b), are critical determinants at the initiation step for glucosome formation in human cells.…”
Section: Discussionmentioning
confidence: 87%
“…Collectively, we identified in silico several biologically relevant parameters of PFKL (i.e., its intermolecular interaction strength, its effective concentration, its multivalency, and its pre-organization prior to condensate formation) that would regulate the formation of PFKL condensates and their sizes in cells. Accordingly, we propose that, when the scaffolder enzyme of a multienzyme glucosome condensate, PFKL, is subcellularly controlled to present relatively a stronger interaction or a higher effective concentration, regulated to be located in a higher multivalency mimicking environment, or organized to form filamentous or similar structures in a cell, the formation of glucosome condensates would be promoted to orchestrate glucose flux in conjunction with other cellular processes in human cells (Jeon et al ., 2022a; Jeon et al ., 2018; Jeon et al ., 2022b; Kennedy et al ., 2022; Kohnhorst et al ., 2017). Considering our study was done in silico with stochastic modeling approaches, we offer a possibility that any metabolic enzymes might be able to form spatially resolved condensates, but at different degrees, in human cells particularly when their biological and physical properties are perturbed acutely and/or dysregulated chronically in human cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, interactions between cyclin dependent kinases (CDKs) and their associated cyclins are essential to regulate subcellular locations, expression levels, and/or enzymatic activities of glycolytic enzymes, including PFK1 and pyruvate kinase muscle isoform 2, for cell cycle progression (10,(12)(13)(14). Importantly, we have recently revealed that multienzyme glucosome assemblies, that regulates glucose flux at subcellular levels (4,5,15), dynamically oscillate in space and time during a cell cycle (16). However, it has remained elusive which regulatory mechanisms ensure tight control over glucosome assemblies and their dynamics during cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%